Hubungan Dukungan Keluarga dengan Kemandirian Perawatan Diri Anak Retardasi Mental di SLB BUKESRA Banda Aceh - Cindi Amelia Putri; Syukriadi Syukriadi; Mansuriza Mansuriza (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Self-care independence is an essential aspect that must be developed so that children can live more independently and achieve a better quality of life. This is based on the vital role of the family in facilitating growth, development, and the formation of independence, especially for children with special needs such as those with intellectual disabilities. Children with intellectual disabilities often experience limitations in adaptive and intellectual abilities, making family support a key factor that helps them learn to perform daily activities independently. This study aims to determine the relationship between family support and self-care independence among children with intellectual disabilities at SLB Bukesra Banda Aceh. The research used a quantitative method with a descriptive-analytic design and a cross-sectional approach. The sample consisted of 40 children with intellectual disabilities selected through purposive sampling from a total of 69 registered students. The research instruments were family support and self-care independence questionnaires using the Guttman scale. The study was conducted from June 1 to June 7, 2025. The results showed that most children received good family support (82.5%) and demonstrated good self-care independence (60%). The bivariate analysis using the Chi-Square test indicated a significant relationship between family support and self-care independence (p-value = 0.001, p < 0.05). Based on these findings, it can be concluded that family support plays a crucial role in improving the self-care independence of children with intellectual disabilities. Therefore, parents are encouraged to provide consistent emotional, appreciation, instrumental, and informational support to help their children learn to care for themselves independently. Self-care independence is an essential aspect that must be developed so that children can live more independently and achieve a better quality of life. This is based on the vital role of the family in facilitating growth, development, and the formation of independence, especially for children with special needs such as those with intellectual disabilities. Children with intellectual disabilities often experience limitations in adaptive and intellectual abilities, making family support a key factor that helps them learn to perform daily activities independently. This study aims to determine the relationship between family support and self-care independence among children with intellectual disabilities at SLB Bukesra Banda Aceh. The research used a quantitative method with a descriptive-analytic design and a cross-sectional approach. The sample consisted of 40 children with intellectual disabilities selected through purposive sampling from a total of 69 registered students. The research instruments were family support and self-care independence questionnaires using the Guttman scale. The study was conducted from June 1 to June 7, 2025. The results showed that most children received good family support (82.5%) and demonstrated good self-care independence (60%). The bivariate analysis using the Chi-Square test indicated a significant relationship between family support and self-care independence (p-value = 0.001, p < 0.05). Based on these findings, it can be concluded that family support plays a crucial role in improving the self-care independence of children with intellectual disabilities. Therefore, parents are encouraged to provide consistent emotional, appreciation, instrumental, and informational support to help their children learn to care for themselves independently.